An integrated maintenance policy for reducing downtime of the carton erector machine in the lubricants industry - Febriza Imansuri; Sabit Iqbal Maulana; Fredy Sumasto (Universitas Sultan Ageng Tirtayasa, 2026)
Maintenance is essential to sustain machine operation and prevent performance degradation caused by continuous use in production processes. In the lubricant production line, the high downtime of the carton erector machine indicates the need for a more effective maintenance policy, particularly for failure-prone components. This study aims to formulate preventive maintenance recommendations by identifying critical components, determining appropriate maintenance actions through the integration of Pareto analysis, Failure Mode and Effects Analysis (FMEA), and Reliability-Centered Maintenance (RCM), and establishing component replacement intervals to reduce downtime associated with age-related failures. The results of the study show that the proposed approach reduces downtime for critical components of the carton erector machine by 58.53%, exceeding the reductions reported in previous studies, which ranged from 35% to 45%. In addition, a replacement interval of 10,000 minutes was found to better reflect the specific degradation characteristics of critical components. These findings highlight that maintenance policies for highly utilized machines should not rely primarily on breakdown maintenance, especially for critical components with high failure vulnerability. This study contributes by proposing an adaptive maintenance framework that integrates scheduled maintenance with component degradation characteristics. The proposed approach is relevant not only to lubricant manufacturing companies but also to other industrial sectors that depend on highly utilized machinery, where even short downtime can significantly affect operational reliability, productivity, and cost efficiency.